2018
DOI: 10.3390/sym10110644
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-2 Protease Structure by Studying Its Asymmetry at the Different Levels of Protein Description

Abstract: HIV-2 protease (PR2) is a homodimer, which is an important target in the treatment of the HIV-2 infection. In this study, we developed an in silico protocol to analyze and characterize the asymmetry of the unbound PR2 structure using three levels of protein description by comparing the conformation, accessibility, and flexibility of each residue in the two PR2 chains. Our results showed that 65% of PR2 residues have at least one of the three studied asymmetries (structural, accessibility, or flexibility) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Our structural-alphabet-based approach highlighted that 35% of unbound PR2 positions are asymmetric. In the unbound and bound structures, the asymmetric positions are distributed throughout the structure, particularly in the interface region and in the flap, fulcrum, elbow, and αhelix regions and the binding site [31,33]. Thus, the crystallographic PR2 structure exhibits structural asymmetry in its backbone, and this property is also found in the unbound structure.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our structural-alphabet-based approach highlighted that 35% of unbound PR2 positions are asymmetric. In the unbound and bound structures, the asymmetric positions are distributed throughout the structure, particularly in the interface region and in the flap, fulcrum, elbow, and αhelix regions and the binding site [31,33]. Thus, the crystallographic PR2 structure exhibits structural asymmetry in its backbone, and this property is also found in the unbound structure.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of the crystallographic structures of PR2 have shown that the two monomers do not exhibit the same global and local conformations, indicating that in crystallographic structures, PR2 exhibits structural asymmetry [27][28][29][30][31][32]. This structural asymmetry is translated by slightly different orientation of its two monomers, quantified by a two-fold axis of 178.20°to 179.80°and a root mean square deviation (RMSD) of 0.35 to 1.02 Å [27][28][29][30]33]. The largest deviations between the two monomers are located in the tail, elbow, and flap regions [27][28][29][30][31]33].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations